Comparison of the long‐term outcome of two therapeutic strategies for the management of abdominal abscess complicating Crohn's disease: percutaneous drainage or immediate surgical treatment. (24th October 2013) - Lobatón, T.; Guardiola, J.; Rodriguez‐Moranta, F.; Millán‐Scheiding, M.; Peñalva, M.; De Oca, J.; Biondo, S.
Abstract: Aim: The management of abdominal abscesses complicating Crohn's disease is complex and involves a difficult choice between medical, radiological and surgical procedures. The long‐term outcome was compared for two strategies for the management of abdominal abscess: percutaneous drainage (PD) followed by rescue surgery in the case of failure vs direct immediate surgery (IS). We also compared the results of IS with surgery performed after PD failure. Methods: We retrospectively identified 44 patients with Crohn's disease with an abdominal abscess from January 2000 to December 2009. Therapeutic success was defined as abscess resolution and no reappearance within 1 year of follow‐up. Results: The first therapeutic approach was PD in 22 cases and IS in the other 22 cases. IS had a higher therapeutic success rate than PD (95.5% vs 27.2% respectively; P  <   0.001). PD was the only independent variable related to treatment failure in the multivariate analysis after adjustment for possible confounders such as abscess size, multilocularity, presence of fistula and corticosteroid use (OR 88.26, 95% CI 7.38–1055.36; P  <   0.001). Surgery after failure of PD ( n  =   16) was associated with longer total hospitalization (56.12 ± 35.89 vs 27.52 ± 15.11 days; P  =   0.017) and longer postoperative stay (44.0 ± 83.7 vs 14.3 ± 30 days; P  =   0.179) and needed a second operation more often (5/16, 31% vs 1/22, 4.5%; P  =   0.065) than IS. Conclusions: Percutaneous drainage provided durable abscess resolution in only one‐third of the patients compared with more than 90% of those treated with IS. In addition, surgery performed after PD failure results in a poorer outcome than IS.